Are you more risk-seeking when helping others? Effects of situational urgency and peer presence on prosocial risky behavior - Liu, Changlin; Xiao, Xiao; Pi, Qiao; Tan, Qianbao; Zhan, Youlong (Frontiers in Psychology, 2023)
Introduction Prosocial risky behavior (PRB) proposes that individuals take risks for others’ benefits or social welfare, and that this may involve trade-offs between risk and social preferences. However, little is known about the underlying cognitive mechanisms of risk-seeking or aversion during PRB. Methods This study adopted the dilemma-priming paradigm to examine the interaction between the risk levels of personal cost and situational urgency on PRB (Experiment 1, N = 88), and it further uncovered the modulation of the risk levels of failure (Experiment 2, N = 65) and peer presence (Experiment 3, N = 80) when helping others. Results In Experiment 1, the participants involved in risky dilemmas made more altruistic choices for strangers in urgent situations compared to those for strangers in non-urgent situations. However, increasing the risk levels of personal cost decreased the frequencies of help offered to strangers in urgent situations. Experiment 2 further established that, similar to the risk of personal cost, increasing the risk levels of failure when helping others also decreased the frequencies of help offered to strangers in urgent situations. Furthermore, in dilemmas involving a low-risk personal cost, Experiment 3 showed that peer presence encouraged the participants to make more altruistic choices when providing help to strangers in non-urgent situations. Discussion Individuals demonstrate obvious risk-seeking behavior when helping others and that both non-urgent situations and peer presence weaken the effect of increased risk aversion on PRB in a limited manner.